2015
DOI: 10.1007/s11011-015-9681-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological manifestations in children with Sydenham’s chorea after adjunct intravenous immunoglobulin and standard treatment

Abstract: This was an exploratory study comparing neuropsychological manifestations of Sydenham's chorea (SC), 6 months after initiation of treatment, in children who had received intravenous immunoglobulins as an adjunct to standard treatment, with those who had received standard treatment. We included a non-SC control group for comparison. We hypothesized that compared to controls, children with SC who had received prior intravenous immunoglobulins would demonstrate less pronounced impairments compared to those who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 42 publications
0
8
1
Order By: Relevance
“…Concerns for this study include lack of placebo control arm, use of a non-validated rating scale, and failure of the blinded observer to perform the initial evaluation at the beginning of the protocol. In a follow-up of these patients, it has been suggested that there might be a difference in executive function at 1, 3, and 6 months between those subjects treated with IVIG + haloperidol compared with haloperidol alone 65. Statistical analyses included a comparison to a “healthy” control group, rather than a simple comparison of the original cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…Concerns for this study include lack of placebo control arm, use of a non-validated rating scale, and failure of the blinded observer to perform the initial evaluation at the beginning of the protocol. In a follow-up of these patients, it has been suggested that there might be a difference in executive function at 1, 3, and 6 months between those subjects treated with IVIG + haloperidol compared with haloperidol alone 65. Statistical analyses included a comparison to a “healthy” control group, rather than a simple comparison of the original cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…Six months after treatment, the IVIG group showed fewer behavior difficulties, less impulsivity, and better cooperation and executive functioning compared to the standard treatment group. 122 Studies of IVIG treatment of the streptococcal-related autoimmune disease, PANDAS, have been mixed. One small study reported improvement in neuropsychiatric symptoms including anxiety, depression, obsession, compulsion, impairment, and overall severity after IVIG (n=9) or plasmapheresis (n=10).…”
Section: 121mentioning
confidence: 99%
“…Choreiform movements are non-rhythmic, involuntary, often asymmetrical, and disappear with sleep. Concurrent muscular weakness and emotional disturbances (crying, restlessness, obsessive-compulsive symptoms, rare psychosis) can occur [70]. Alternate diagnoses should be excluded.…”
Section: Current Epidemiology Of Gas Arf and Rhd Around The Worldmentioning
confidence: 99%